Residues of Veterinary Drugs in Animal Products Commercialized in the Border Region of Brazil, Argentina, and Uruguay - Soares, Vanessa Mendonça; Pereira, Juliano Gonçalves [UNESP]; Barreto, Fabiano; Jank, Louise; Rau, Renata Batista; Ribeiro, Cristina Belíssimo Dias; Castilhos, Tamara dos Santos; Tomaszewski, Caroline Andrade; Hillesheim, Daniel Rodrigo; Mondadori, Rafael Gianella; Tadielo, Leonardo Ereno [UNESP]; Santos, Emanoelli Aparecida Rodrigues dos; et al. (Elsevier, 2022)
ABSTRACT: The traffic in international animal products can become a public health hazard when legal import sanitary procedures are not followed. In Brazil, due to its extensive border area, the importation of animal products is a common practice in many areas, especially in Rio Grande do Sul, a state that borders Argentina and Uruguay. The objective of this study was to evaluate the presence of veterinary drug residues (antibiotics and antiparasitics) in animal products consumed in Rio Grande do Sul. The presence of residues of veterinary antibiotics and antiparasitics was assessed in 189 meat (beef, pork, and chicken), processed dairy, and meat product samples bought in Argentina (n = 90) and Uruguay (n = 99). Residues of these veterinary drugs were detected in 50 (26.45%) of the samples; 28 samples (14.81%) had antibiotic residues, and 22 samples (11.64%) had antiparasitic residues. Of the 50 positive samples, 40% (15 from Argentina and 5 from Uruguay) had residues above the maximum residue limits (MRLs). Of these 20 samples, 12 had antiparasitic residues above the MRLs (11 beef samples had ivermectin and 1 pork sample had ivermectin and doramectin) and 8 had antibiotic residues above the MRLs (2 pork and 2 sausage samples had doxycycline, 2 cheese samples had doxycycline and chlortetracycline, 1 poultry meat sample had chloramphenicol, and 1 cheese sample had monensin). Because of the potential toxic effects on humans and the potential for pathogens to develop antibiotic resistance, the presence of these residues above the MRLs is a potential risk to public health. The negative impact of consumption of imported animal products can be reduced by implementation of an effective surveillance system and educational campaigns for the general population.
Keywords: Animal products; Border; Chemical residues; Chloramphenicol; Ivermectin